Kreativiti Pereka Tempatan Kuching untuk Menerapkan Rekaan Pua Kumbu ke dalam Dekorasi Hiasan Dalaman - Wong, Catherine Sie Nguk. (Universiti Malaysia Sarawak (UNIMAS), 2007)
This research is to study the creativity of local designers in applying Pua Kumbu to interior design such as decorations in restaurants, residential units, offices, and hotels in Kuching. Thus, this research hopes to serve as a reference and inspiration to the researcher and the next generation of designers in their application of Pua Kumbu in interior design.